IMPLEMENTASI AREA TRAFFIC CONTROL SYSTEM DALAM KONTEKS KEPATUHAN BERLALU LINTAS DI KOTA SERANG - Diki Fahrul Alam; Ronni Juwandi; Ria Yuni Lestari (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2021)
ABSTRACT The purpose of this study was to determine the implementation of the Area Traffic Control System (ATCS) in the context of traffic compliance in Serang City. Data collection for this research was carried out at the Banten Province Transportation Agency as the party that manages ATCS in Serang City, Serang City Police, and area Serang City Intersection using a descriptive qualitative approach. The researcher Collect the data by using observation, interview, and documentation techniques. The result of this research is that the motorists responded positively to the presence of ATCS in Serang City because the presence of ATCS was a form of progress in its own right in Serang City. Motorists are aware of ATCS at several intersection points in Serang City, and drivers feel that they are being watched so they are afraid to violate traffic. However, drivers regretted that the loudspeakers used were not heard clearly and warnings or reprimands were only recorded. This makes a lot of motorists feel indifferent and violate traffic when they are at the Serang City Intersection with ATCS installed. However, the implementation is still not optimal, because the goals and objectives have not been achieved. There are still many traffic violations, then a lack of human resources in terms of numbers or inadequate education, a lack of time resources, and a lack of financial resources. This is also added to the damage to the equipment and the absence of sanctions from ATCS which are the inhibiting factors in implementing ATCS. The determining factor is the support and respect of the community for the Serang city government for the procurement of ATCS. Keyword: Implementation, ATCS, Compliance, Traffic